Family, social and organizational support among healthcare professionals during COVID-19 pandemic in selected districts of Nepal - Sapkota, Abja; Sedhain, Arun; Gachhadar, Rashmi; Bhattarai, Gandhi Raj (Journal of Chitwan Medical College, 2021)
Background: One of the important factors that could affect better health care delivery during COVID-19 pandemic remains the better working environment for healthcare professionals. Support provided by the family, society and workplace would play an important role to boost their work performance. This study aimed to assess the perception of family, social and organizational support among the frontline healthcare professionals during COVID-19 pandemic in selected districts of Nepal. Methods: This descriptive cross-sectional study consisted of 325 healthcare professionals working in different hospitals of Bagmati province of Nepal. Data were collected using self-administered structured questionnaire via Google form. Collected data were analyzed using descriptive and inferential statistics. Results: Adequate support was perceived by 50.5% of the respondents and the mean overall perceived support score was 98.83±11.2. The highest perceived score (37.25±4.37) was on family support domain followed by social support (33.55±4.08) and the organizational support (28.01±5.7). Factors like advanced age, higher education level, male sex, and working in the government hospitals showed significant association with perceived family and social support. Type of the institutions and tenure status were main predictors for the perception of adequate organizational support. Conclusions: For their inspiration to work, adequate support to healthcare professionals not only from family but also from the society and organizational level would be quite important. Apart from some non-modifiable factors, other factors like adequate and timely provision of monthly salary, guaranteed medical treatment if they fall sick have been found to play important role to keep the them motivated to their work.